2008
DOI: 10.3748/wjg.14.1425
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for transfusion and postoperative outcomes in orthotopic liver transplantation: A meta-analysis on aprotinin

Abstract: INTRODUCTIONOrthotopic liver transplantation (OLT) has become the first choice approach for the treatment of patients with end-stage liver diseases [1] . However, despite great improvements in graft preservation, surgical skills, anesthetic techniques and perioperative management [2,3] , OLT is still associated with severe bleeding and considerable transfusion requirements, which in turn greatly contribute to the peri-operative morbidity and mortality [4] . Severe bleeding in OLT occurs for several reasons, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…In contrast to other groups, we have shown no increase in red blood cell or other blood component transfusion requirements since the withdrawal of APRO from our routine practice . A recent Cochrane systematic review also showed that APRO, recombinant factor VIIa, and TEG may potentially reduce blood loss and transfusion requirements, but there was no difference in transfusion requirements when APRO and tranexamic acid were compared .…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In contrast to other groups, we have shown no increase in red blood cell or other blood component transfusion requirements since the withdrawal of APRO from our routine practice . A recent Cochrane systematic review also showed that APRO, recombinant factor VIIa, and TEG may potentially reduce blood loss and transfusion requirements, but there was no difference in transfusion requirements when APRO and tranexamic acid were compared .…”
Section: Discussioncontrasting
confidence: 68%
“…Since the late 1980s, aprotinin (APRO), a serine protease an inhibitor of plasmin and, at higher doses, kallikrein, have been used at many institutions to reduce the incidence of bleeding caused by fibrinolysis during OLT . The first multicenter, randomized study by Porte et al showed that the intraoperative use of APRO in patients undergoing OLT significantly reduced blood transfusion requirements, and other groups have reported similar findings …”
mentioning
confidence: 98%
“…First, they have the potential to require large amounts of blood products. In a meta‐analysis of 4 studies comparing transfusion requirements during liver transplantation, the mean number of transfused RBC units ranged from 2 to 14, and the mean number of fresh frozen plasma units ranged from 1 to 28 31. Second, they could potentially benefit from the immunosuppression that may accompany RBCs that have been stored for longer periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…was withdrawn from the market amid concerns over excess mortality in 2007 but it is available once more, following a revoked suspension in 2012 by the European Medicines Agency [90,91] . A meta-analysis of 7 studies in LT demonstrated significantly lower RBC and FFP requirements patients who received aprotinin compared with controls but no differences in terms of reoperation rates, thrombotic events or mortality [92] . Tranexamic acid and epsilon aminocaproic acid (EACA) are lysine analogues that adhere to lysine binding sites on plasminogen preventing its conversion to plasmin.…”
Section: Antifibrinolyticsmentioning
confidence: 99%